How do Key Stage Two teachers support children who are mathematically gifted in an international school in Dubai? - Crowther-Walsh, Victoria (2016)
The aims of this research were to find out how teachers support mathematically gifted children in an international school in Dubai. The methodological approach adopted was through semi-structured interviews. The results from this research suggest that teachers in my school lack: confidence, awareness and strategies to support mathematically gifted children. Further recommendations of this study would be to examine other schools within the UAE.